2021
DOI: 10.1039/d1ra00766a
|View full text |Cite
|
Sign up to set email alerts
|

Renewable bio-based adhesive fabricated from a novel biopolymer and soy protein

Abstract: The crosslinking reaction process of SPI/EHL-ESO adhesives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 50 publications
0
14
0
1
Order By: Relevance
“…The qualities of individual starch are mainly reliant on its botanical origin, even though it is usually referred to as solitary [ 140 ]. Specifically, it is present in high amounts in legumes, cereal grains, tubers, and roots [ 141 ] and is found in the tissue of fruits and vegetables [ 142 ]. Despite its availability, rice (in Asia), wheat (in the United States and Europe), corn (in the United States and Europe), tapioca (in Brazil, Thailand, and Indonesia), and potato (in Europe) are the only economically sustainable sources of starch [ 143 ].…”
Section: Biopolymers For Food Applicationsmentioning
confidence: 99%
“…The qualities of individual starch are mainly reliant on its botanical origin, even though it is usually referred to as solitary [ 140 ]. Specifically, it is present in high amounts in legumes, cereal grains, tubers, and roots [ 141 ] and is found in the tissue of fruits and vegetables [ 142 ]. Despite its availability, rice (in Asia), wheat (in the United States and Europe), corn (in the United States and Europe), tapioca (in Brazil, Thailand, and Indonesia), and potato (in Europe) are the only economically sustainable sources of starch [ 143 ].…”
Section: Biopolymers For Food Applicationsmentioning
confidence: 99%
“…Innym interesującym wykorzystaniem epoksydowanych olejów roślinnych jest modyfikacja właściwości klejów na bazie białka sojowego lub mąki sojowej. W tym celu otrzymano prepolimer [49,50] z ESO i hydrolizowanej enzymatycznie ligniny (EHL) lub pochodną ESO [51], będącą produktem częściowego otwarcia pierścienia ESO kwasem fosforowym. Oba te modyfikatory pełniły rolę wielofunkcyjnego środka sieciującego, o wysokiej reaktywności.…”
Section: Epoksydowane Oleje Roślinne Jako Substraty żYwicunclassified
“…The study showed that the bending strength and internal bond strength of particleboards produced with the use of PVAc glue are lower than for panels produced with the use of UF resin [ 9 ]. In recent years, a considerable amount of research has been done on natural adhesives from sustainable resources such as lignin [ 10 , 11 , 12 ], soybean [ 12 , 13 , 14 ], condensed tannins [ 15 , 16 , 17 , 18 ], and suberinic acids [ 19 ] in the partial of full replacement of PF. Condensed tannins (CTs) from lignocellulosic biomass could potentially be eco-friendly substitutes for phenol in adhesives due to the high reactivity of CTs toward aldehydes, including formaldehyde [ 20 ].…”
Section: Introductionmentioning
confidence: 99%